Newborn Screening for G6PD Deficiency in Xiamen, China: Prevalence, Variant Spectrum, and Genotype-Phenotype Correlations - Wang, Xudong; Xia, Zhongmin; He, Ying; Zhou, Xiaoman; Zhang, Haixia; Gao, Chunliu; Ge, Yunsheng; Cai, Xiaofang; Zhou, Yulin; Guo, Qiwei (Frontiers in Genetics, 2021)
Background: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is a common inherited enzymatic defect. The purpose of this study was to assess the incidence and mutational spectrum of G6PD deficiency in Xiamen and explore the effect of temperature on G6PD biochemical screening and potential correlations involving G6PD mutations and G6PD enzyme activity. Methods: A total of 99,546 newborns were screened for G6PD deficiency by modified fluorescent spot test (FST) in Xiamen Maternal and Child Health Hospital, and then the suspected positive patients were recalled for the confirmatory diagnosis testing of G6PD activity or G6PD mutations by using quantitative G6PD enzymatic assay or MeltPro® G6PD assay. Results: In the first screening, 1,256 newborns were suspected to be G6PD-deficient. Of these, 1,051 were diagnosed as G6PD deficiency, with an overall incidence of 1.39% in Xiamen. Among the 1,013 neonates genotyped using the MeltPro® G6PD assay, 851 had either hemizygous, heterozygous, homozygous, or compound heterozygous mutations, yielding a positive predictive value of 84.01%. In total, 12 mutations and 32 genotypes were identified, and the six most common variants were c.1376G>T, c.1388G>A, c.95A>G, c.1024C>T, c.871 G>A, and c.392 G>T, which accounted for approximately 94% of the identified alleles. For each mutation, the distribution of G6PD enzyme activity in males was narrower than that in females, and enzyme activity in males was lower than that in females. Importantly, we demonstrate that the temperature of sample delivery and storage influenced the accuracy of G6PD enzyme activity in biochemical screening. Conclusions: This study systematically demonstrated the prevalence and mutational spectrum of G6PD deficiency, as well as genotype-phenotype association, which can be of great significance for the prevention and control of G6PD deficiency in Xiamen. Moreover, combining biochemical screening with molecular screening, as well as the cold-chain transportation of sample delivery, would be a reasonable strategy and a promising practice in newborn screening programs.